Proceedings of 2nd International Electronic Conference on Sensors and Applications 2015
DOI: 10.3390/ecsa-2-a001
|View full text |Cite
|
Sign up to set email alerts
|

Piezoresistive membrane surface stress sensors for characterization of breath samples of head and neck cancer patients

Abstract: For many diseases, where a particular organ is affected, chemical by-products can be found in the patient's exhaled breath. Breath analysis is often done using gas chromatography and mass spectrometry, but interpretation of results is difficult and time-consuming. We performed characterization of patients' exhaled breath samples by an electronic nose technique based on an array of nanomechanical membrane sensors. Each membrane is coated with a different thin polymer layer. By pumping the exhaled breath into a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Cancer is one of the most sever diseases in the world with the highest mortality. As a preliminary study, Loizeau et al demonstrated the cancer diagnosis through breath analysis using an MSS array [ 154 , 155 ]. They used 16 different polymers as a receptor material, which have different chemical and physical properties to express a wide range of chemical selectivity.…”
Section: Applications For Artificial Olfaction Using Mssmentioning
confidence: 99%
“…Cancer is one of the most sever diseases in the world with the highest mortality. As a preliminary study, Loizeau et al demonstrated the cancer diagnosis through breath analysis using an MSS array [ 154 , 155 ]. They used 16 different polymers as a receptor material, which have different chemical and physical properties to express a wide range of chemical selectivity.…”
Section: Applications For Artificial Olfaction Using Mssmentioning
confidence: 99%